Grotifer: A new electric field instrument design to address the need for highly accurate three-component electric field measurements - Lejosne, Solène; Auslander, David M.; Bonnell, John W.; Klumpar, David M.; Mozer, Forrest S.; Pankow, David H.; Sample, John G. (Frontiers in Astronomy and Space Sciences, 2022)
Accurate knowledge of the full, three-dimensional electric field vector is of fundamental importance in understanding electrodynamics of a vast variety of space plasmas. However, heliophysics research still lacks access to the reliable parallel electric field measurements required to close many significant science questions. This uncertainty represents a significant barrier to progress in the field. The only way to close this major observational gap is a profound change in electric field instrument design. A new electric field instrument called Grotifer is now being designed to address the need for highly accurate three-dimensional electric field measurements while enabling lower cost missions and constellation missions in deep space. Grotifer (Giant rotifer) is a reference to the rotifer, also known as the “wheel animalcule”. Similarly, Grotifer consists of mounting detectors on two rotating plates, orthogonal to each other, on a non-rotating central body. The two rotating plates provide continuous high-accuracy three-dimensional measurements of both electric fields and magnetic fields. The Grotifer design leverages more than fifty years of expertise in delivering highly accurate spin plane electric field measurements, while overcoming inaccuracies generated by spin axis electric field measurements. Our current efforts focus on designing Grotifer as a SmallSat (27U CubeSat). That said, Grotifer could also become part of the payload on a much larger platform. In the future, one could imagine fleets of Grotifers studying electrodynamics at many points, facilitating differentiation between spatial and temporal dynamics. Plasma detectors could also be added to the rotating plates to cover the full phase space better than is done on spinning spacecraft, leading to more complete correlation studies of the fields and plasmas.